2021
DOI: 10.1186/s12913-021-06316-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of loss of PEPFAR support on HIV services at health facilities in low-burden districts in Uganda

Abstract: Background Although donor transitions from HIV programs are more frequent, little research exists seeking to understand the perceptions of patients and providers on this process. Between 2015 and 2017, PEPFAR implemented the ´geographic prioritization´ (GP) policy in Uganda whereby it shifted support from 734 ‘low-volume’ facilities and 10 districts with low HIV burden and intensified support in select facilities in high-burden districts. Our analysis intends to explore patient and provider per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…This is alarming as there is a plan for donors to progressively transition from supporting the Kenyan health sector generally, and primary healthcare facilities specifically. Donor transition is expected to put additional fiscal pressure to LMIC health systems, threatening service delivery, and thus requiring them to device ways replace diminishing donor support with domestic resources [21,22]. Third, consistent with previous findings [12,23], funds flow to public health facilities from prepaid sources (county and national government allocations, and NHIF disbursements), are characterized by delays in disbursements.…”
Section: Discussionsupporting
confidence: 75%
“…This is alarming as there is a plan for donors to progressively transition from supporting the Kenyan health sector generally, and primary healthcare facilities specifically. Donor transition is expected to put additional fiscal pressure to LMIC health systems, threatening service delivery, and thus requiring them to device ways replace diminishing donor support with domestic resources [21,22]. Third, consistent with previous findings [12,23], funds flow to public health facilities from prepaid sources (county and national government allocations, and NHIF disbursements), are characterized by delays in disbursements.…”
Section: Discussionsupporting
confidence: 75%
“…This is alarming as there is a plan for donors to progressively transition from supporting the Kenyan health sector generally, and primary healthcare facilities speci cally. Donor transition is expected to put additional scal pressure to LMIC health systems, threatening service delivery, and thus requiring them to device ways replace diminishing donor support with domestic resources (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that between June 2015 and December 2017, of the PEPFAR-recruited HIV workforce, 694 were absorbed into mainstream GoU employment ( PEPFAR plans to transition all HWs it recruited under the intervention to the GoU payroll to support accelerated HIV service delivery across Uganda in line with UNAIDS's 95-95-95 targets [7]. However, there is little empirical understanding of the drivers of retention of HWs once they are absorbed into the Ugandan public service, given their prior private sector work experience.…”
Section: Pepfar Hiv Workforce Expansion Interventionmentioning
confidence: 99%
“…Uganda is heavily dependent on global health initiatives (GHIs), notably President's Emergency Plan for AIDS Relief (PEPFAR) and the Global Fund for AIDS, Tuberculosis, and Malaria (Global Fund) in its national HIV response [4]. Since 2004, PEPFAR has supported Uganda's national HIV response by rapidly expanding ART coverage and rolling out HIV prevention initiatives such as safe male circumcision (SMC) and pre-exposure prophylaxis (PrEP) [2]- [7].…”
Section: Introductionmentioning
confidence: 99%